Book Review: “Medicine-Based Informatics and Engineering” Lecture Notes in Bioengineering, Springer, 2022 - Duque-Méndez, Néstor Darío (Revista Mexicana de Ingenieria Biomedica, 2022)
This paper is an original review of the book "Medicine-Based Informatics and Engineering" published in Springer's Lecture Notes in Bioengineering collection, in 2022, whose editors are Franco Simini and Pedro Bertemes-Filho. The review aims to synthesize the content of the papers presented in the chapters focusing on the solutions developed. The editors, from the diversity of the contributions, envision the integration of visions, in what they call "Medical Engineering".